Immunosuppressive agents for frequently relapsing/steroid-dependent nephrotic syndrome in children: a systematic review and network meta-analysis - Zhu, Yu; Chen, Junyi; Zhang, Yao; Wang, Xiaoai; Wang, Jingjing (Frontiers in Immunology, 2024)
Aim This study aimed to systematically compare the efficacy of various immunosuppressive agents in treating pediatric frequently relapsing or steroid-dependent nephrotic syndrome (FRSDNS). Methods We conducted systematic searches of PubMed, Embase, the Cochrane Library, and the Web of Science up to May 23, 2023. Outcome measures included relapses within 1 year, mean cumulative exposure to corticosteroids, patients with treatment failure at 1 year, relapse-free survival during 1 year, and adverse events. The quality of the included studies was evaluated using the modified Jadad scale, the Methodological Index for Non-Randomized Studies (MINORS), and the modified Newcastle-Ottawa Scale (NOS). Results Rituximab was found to be the most likely (92.44%) to be associated with the fewest relapses within 1 year and was also most likely (99.99%) to result in the lowest mean cumulative exposure to corticosteroids. Rituximab had the highest likelihood (45.98%) of being associated with the smallest number of patients experiencing treatment failure at 1 year. CsA was most likely (57.93%) to achieve the highest relapse-free survival during 1 year, followed by tacrolimus (26.47%) and rituximab (30.48%). Rituximab showed no association with serious side effects and had comparable adverse effects to ofatumumab and tacrolimus. Conclusion Rituximab may be the most favorable immunosuppressive agent for treating pediatric FRSDNS. Nephrologists should consider this drug, along with their clinical experience, patient characteristics, and cost considerations, when choosing a treatment approach.